What Shall We Do With a Sea of Plastics? A Systematic Literature Review on How to Pave the Road Toward a Global Comprehensive Plastic Governance Agreement - Cowan, Emily; Tiller, Rachel (Frontiers in Marine Science, 2021)
In February 2022, the United Nations Environmental Assembly (UNEA) is expected to mandate negotiations for a legally binding plastic agreement. In preparations for such discussions, it is important to understand the academic research behind what a global treaty on plastic will require to succeed. Therefore, a systematic literature review was conducted on 64 peer-reviewed articles published before July 4th, 2021, that focused on global plastic governance and avenues to mitigate our pollution crisis. Once reviewed, the articles were organized into a series of four main categories: (1) plastic pollution overview articles, (2) top-down solutions, (3) bottom-up solutions, and finally a (4) global treaty as a solution. The analysis of these articles enabled an overarching review and discussion of what the literature suggested is required for the creation of a global plastics agreement. First, the researchers argued that previous global plastics governance literature is characterized by an optimist governance perspective, i.e., a view of governance as a problem-solving mechanism. Second, global plastics governance as a research field could make headway by engaging in further empirical investigation of current negotiations and solutions at the national level, especially in developing nations. In the end we found that a global agreement is feasible if it allows for multi-stakeholder solutions involving industry, governance, stakeholders, and citizens.